That will depend on the plus or minus value of 12 which has not been given.
You cannot find the answer to an expression!!! An expression needs to be EQUATED' to a value, for another value to be found. 2x^(2) + 5x + 12 is an EXPRESSION. Impossible to find an value for 'x'. However, 2x^(2) + 5x + 12 = 0 is an EQUATION and a result can be calculated.
5X - 2Y X = 9 Y = 4 5(9) - 2(4) 45 - 8 37 is the value
5x + 3 = -12 5x =-12-3 =-15 x = -3
-5x + y = -12- 3x + 6y = -12Since both of expressions have a value of -12, their sum is - 24. This is true only whenx = 20/9 and y = -8/9.-5x + y = -12y = 5x - 12- 3x + 6y = -12-3x + 6(5x - 12) = -12-3x + 30x - 72 = -1227x = 60x = 60/27x = 20/9y = 5x - 12y = 5(20/9) - 12y = 100/9 - 12y = (100 - 108)/9y = -8/9
It is impossible to give the value of t when it is not defined.
-13 Plug 5 in and multiply it by -5 which equals -25 12 - 25 = -13
5x=4012y=84124
-42
You cannot find the answer to an expression!!! An expression needs to be EQUATED' to a value, for another value to be found. 2x^(2) + 5x + 12 is an EXPRESSION. Impossible to find an value for 'x'. However, 2x^(2) + 5x + 12 = 0 is an EQUATION and a result can be calculated.
5X - 2Y X = 9 Y = 4 5(9) - 2(4) 45 - 8 37 is the value
5x - 3 = 12 Add 3 to both sides: 5x = 15 Divide both sides by 5: x = 3
317
Though 10x +24 is an expression and it can not be evaluate, we can write 10x+24=2 • (5x + 12)
5x + 3 = -12 5x =-12-3 =-15 x = -3
When x equals 8, the value of 5x would be 5 times 8, which is 40.
3(x + 2) = 5x - 12 3x + 6 = 5x - 12 6 = 2x - 12 6 + 12 = 2x x = 9
6x - 3x = 5x - 10x + 12 6x - 3x - 5x + 10x = 12 8x = 12 8x/8 = 12/8 x = 12/8 = 3/2 x = 1.5